Comparative studies of interferon and three antiviral agents on neurotropic and oncogenic herpesviruses. - Daniel, M D (1980)
The antiviral effects of four compounds, phosphonoacetate, phosphonoformate, acycloguanosine, and purified human lymphoblastic interferon, were tested against two neurotropic herpesviruses, herpesvirus platyrrhine and herpes simplex virus, and two oncogenic herpesviruses, herpesvirus saimiri and herpesvirus ateles. All four compounds induced different degrees of inhibition of these herpesviruses. Phosphonoacetate and phosphonoformate at concentrations of 50 micrograms/ml or greater showed powerful antiviral activities. Interferon was more effective against herpesvirus saimiri and herpesvirus ateles, the two oncogenic viruses. Herpes simplex virus and the oncogenic herpesviruses were effectively inhibited by acycloguanosine, whereas herpesvirus platyrrhine proved to be resistant. The simian herpesviruses required a higher concentration of phosphonoformate, phosphonoacetate, and acycloguanosine for antiviral action. The antiviral action of all four compounds was contingent on the continued presence of the compounds in the infected cell culture medium.